Processamento de fibra de caju por extração de substâncias solúveis seguida de secagem para aplicação como ingrediente em produto plant-based - Saldanha, Gecyene Rodrigues do Nascimento (2022)
Cashew fiber is the by-product obtained after removal of the nut (fruit) and extraction of juice from the stalk, and is usually discarded in the environment or used for animal feed. For its use as an ingredient in food it is recommended the pre-treatment of extraction of soluble substances with sequential cycles of hydration with water and pressing to reduce the acidity, sugar content and aftertaste of cashew juice in the fiber, besides its size, being considered a bottleneck of the process. The objectives of this work were: (i) to evaluate the effect of the pre-treatment steps on the sensorial perception of cashew fiber, (ii) to compare the drying processes using oven with forced air circulation and freeze-drying, and (iii) to evaluate the application of the pre-treated fiber in a croquette type plant-based product. The cashew fiber was processed and sensorially evaluated in each of the five cycles of hydration and pressing employed, using three hydration ratios (fiber : water ratio of 1:1, 1:1.5 and 1:2), followed by pressing in an Expeller type press in each cycle. The collected wet samples were sensorially evaluated by trained tasters, and physical and physicochemical analyses of yield, acidity, pH, total extractable polyphenols, soluble solids, and moisture were performed. The fibers, subsequently dehydrated, were evaluated for water absorption capacity (WAC) and oil absorption capacity (OAC), color (L*, a*, b*), total extractable polyphenols and antioxidant activity. The croquettes formulations were prepared with 30, 40 and 50% freeze-dried dehydrated cashew fiber, and the samples were sensorially evaluated for acceptance and purchase intention and by physicochemical and centesimal composition analyses. The results obtained in the sensory evaluation of wet samples of cashew fiber collected after each washing/pressing cycle indicated that the perception of descriptors related to cashew flavor is weak or very weak after the second cycle, and the process can be optimized by reducing the number of cycles. The proportion of water used did not present a significant difference in relation to sensory perception between the second and the fifth cycle, indicating that it is not necessary to increase the amount of hydration water. The results of the physicochemical analyses (humidity, titratable acidity, soluble solids, pH and polyphenols) also show that it is not necessary to go until the fifth cycle of hydration and pressing to reduce the acidity, the sugar content and the cashew aftertaste, The freeze-drying process of the fiber showed 27% (±0.1) of yield and the obtained fiber had 3.6% (±0.03) of humidity, SAC of 767g/100g (± 23.03) and OWC of 450g/100g (±11.9), 98.42 (± 1.40) of EAG/100g of extractable phenolic compounds. Put the values obtained in the other processes. In the sensory evaluation of the croquettes there was an average acceptance of 7.0 to 8.0 for the three treatments evaluated (30, 40 and 50% of cashew fiber), with overall acceptance of "I liked it a lot", with no significant difference in appearance, flavor and texture, occurring only significant perception (p < 0.05) for characteristic cashew flavor in the formulation with 50% of fiber. The conclusions of this work indicate that the pretreatment of cashew fiber can be optimized for two cycles of hydration followed by pressing. The different drying methods give origin to fibers with different characteristics, however, depending on the application, all can be employed as ingredient in the formulation of food products. The application in croquette type plant-based product can be used in contents of up to 40% cashew fiber.